Death and finitude : toward a pragmatic transcendental anthropology of human limits and mortality - Pihlström, Sami (American philosophy series, 2016)
This book integrates pragmatism and transcendental philosophy in examining the most serious problem defining the human condition, death and mortality. Its analysis of human limits and finitude is intended to be relevant to the concerns of philosophers specializing in, for example, transcendental philosophy, philosophical anthropology, pragmatism, Wittgenstein, and the philosophy of religion. Mortality is studied as providing a necessary framework within which questions concerning the meaningfulness or meaninglessness of human life become possible.